Chāyāvādottara Hindī kavitā : rasa-nikasha para - Caturvedī, Rshikumāra, 1935- (Granthāyana, 1982)
Study of the post-Chayavada Hindi poetry in the context of the rasa (aesthetics) theory of Sanskrit poetics.